Primary Mediastinal Gray Zone Lymphoma in an Immunocompetent Young Adult - Aisyah Wirdah; Yenny Dian Andayani; Mediarty Syahrir; Norman Djamaludin; Krisna Murti; Ali Zainal Abidin (Acta Medica Indonesiana, 2023)
A 28 -year-old man presented to our hospital with a rapidly growing nodule in the left cervical and bilateral axilla with a history of loss of weight. He has been experiencing a nodule in her right cervical since two years ago and had done FNAC and diagnosed extrapulmonary tuberculosis (EPTB), on Examination at left cervical colli; mass size 9cm x 7 cm, mobile, Lymphadenopathy at pre auricular size 3cm x 3cm, lymphadenopathy supraclavicular size 1cm x 0,5 cm. bilateral lymphadenopathy Axila size 4cmx 4cmx 2xcm mobile. The other physical exam was normal. Laboratory test Hb 10,4 d/dL, WBC 14.250/ mm3, LED 78 mm/hours, D-dimer 1,81 ug/mL, Fibrinogen 452 mg/dL. HIV test non-reactive. HbsAg and HCV test negative. CT-Scan Thorax: Enlarged Anterior mediastinal Lymph node with a diameter 0f 2.9 cm, right paratracheal with a diameter of 1,2cm and 1,1 cm, and right perihilar with a diameter of 1,3 cm. and the left perihilar diameter 0,9. And hypodense lesion of the spleen measuring 2,3cm x 1,6 cm. The patient underwent a biopsy with pathology biopsy and immunohistochemistry (IHC), CD 20+. CD 3-, CD 30+ CD79a +, MUM1 +, Ki67 80-90% +, CD15-, BCL6+ and BCL 2+. For this patient, we started an R-CHOP regimen (Rituximab 375 mg/m2 (d1), Cyclophopamid 750 mg/m2 (d1), Doxorubicin 50 mg/m2 (d1), Vincristine1,2 mg/m2 (d1) and 1 Prednisone 100 mg (d1-d5). We presented the patient with PMGZL has achieved a complete response, especially with chemotherapy R-CHOP regimens